(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The texture properties of the four samples of Syrian ore containing zeolite were studied by the analysis of the adsorption-desorption data of nitrogen at 77K. The samples are taken from tell-assis site. The adsorption isotherms for all samples belong to IV type of BDDT classification. Surface areas determined using the BET liner equation, and the standard isotherm methods,i.e, t-plots, α-methods. These methods showed a good agreement. The values of the surface area for samples are (66-100)m2/g. The samples contain pores of different shapes and types. They have mesopores mainly (30-38)Å, and the microporosity are (20-25)%. The values of the characteristic energy of adsorption are in the range of 11.6 -16.4 kJ/mol. تمت دراسة خواص البنية النسيجية لأربع عينات من الخامات الطبيعية في سوريا والحاملة للزيوليت من منطقة تل السيس, وهي من مواقع مختلفة وأعماق مختلفة, وتحمل الأرقام TS-7, TS-9, TS-14, TS-18 تم تحديد السطح النوعي لهذه العينات بطريقة BET وبطرائق المناحي القياسية t-method, -method α, وتم أيضا تحديد توزع المسام. استخدمت تقنية امتزاز النتروجين عند الدرجة 77K بواسطة جهاز امتزاز حجمي آلي مبرمج من نوع Gemini 2375. تبين من خلال الدراسة أن العينات تملك سطحا نوعيا يتراوح بين (66-100 m2 /g), وتظهر قيم السطح النوعي المحسوبة وفق الطرائق المختلفة تطابقا جيدا. إن العينات المدروسة تحتوي بشكل أساسي على مسامات من نوع ميزو, حيث يتراوح نصف قطر المسام لها بين (30-38)Å,وتتراوح نسبة المسام الدقيقة وفق طريقة DR بين (20-25)%, وأن قيمة الطاقة المميزة للإمتزاز تتراوح بين (11.6 – 16.4) kJ/mol.